Monkeypox Patients Living with HIV: A Systematic Review and Meta-Analysis of Geographic and Temporal Variations - Aravind P. Gandhi; Bijaya K. Padhi; Mokanpally Sandeep; Muhammad Aaqib Shamim; Tarun K. Suvvari; Prakasini Satapathy; Abdelmonem Siddiq; Ranjit Sah; Sarvesh Rustagi; Zahraa H. Al-Qaim; Jagdish Khubchandani (MDPI AG, 2023)
This index meta-analysis estimated the pooled prevalence of human immunodeficiency virus (HIV) among individuals with monkeypox (mpox) globally. We searched seven databases: PubMed, Scopus, Web of Science, EMBASE, ProQuest, EBSCOHost, and Cochrane, for human studies published in English till 4 January 2023, as per International Prospective Register of Systematic Reviews (PROSPERO) registration protocol (CRD42022383275). A random effects regression model was used to estimate the pooled prevalence owing to high heterogeneity. The risk of bias in the included studies was assessed using the National Heart, Lung, and Blood Institute (NHLBI) quality assessment tool. The systematic search yielded 677 articles; finally, 32 studies were found eligible for systematic review and 29 studies for meta-analysis. The pooled prevalence of HIV infection was 41% (95% confidence interval [CI], 35-48). All studies were rated as fair or good quality. Studies from Europe and North America reported a high prevalence of HIV infection among individuals with mpox- 41% (95% CI 33-49) and 52% (95% CI 28-76), respectively, while studies from Nigeria, Africa reported a relatively low prevalence of HIV infection of 21% (95% CI 15-26). A history of sexual orientation and sexual partners in the last 21 days must be taken from individuals with mpox to identify the potential source and contacts for quarantining and testing them.